The entrepreneur and small business marketing problem solver - Cohen, William A . (John Wiley, 1991)
Focuses exclusively on the marketing concerns of small businesses. Helps the small business owner be successful in marketing. Each chapter stands alone and covers a specific class of marketing problems. By putting all essential information about marketing at the reader's fingertips, it comprises his best first investment